Delayed PARP-1 Inhibition Alleviates Post-stroke Inflammation in Male Versus Female Mice: Differences and Similarities - Chen, Jian; Li, Xiaoxi; Xu, Siyi; Zhang, Meijuan; Wu, Zhengzheng; Zhang, Xi; Xu, Yun; Chen, Yanting (Frontiers in Cellular Neuroscience, 2020)
Post-stroke inflammation is almost involved in the whole process of stroke pathogenesis, which serves as a prime target for developing new stroke therapies. Despite known sex differences in the incidence and outcome of stroke, few preclinical or clinical studies take into account sex bias in treatment. Recent evidence suggests that poly (ADP-ribose) polymerase (PARP)-1 inhibitor exerts sex-specific neuroprotection in the ischemic stroke. This study was aimed to investigate the effects of delayed PARP-1 inhibition on post-stroke inflammation and possible sexual dimorphism, and explore the possible relevant mediators. In male and female C57BL/6 mice subjected to transit middle cerebral artery occlusion (MCAO), we found that delayed treatment of PARP-1 inhibitor at 48 h following reperfusion could comparably alleviate neuroinflammation at 72 h after stroke. Whereas, the improvement of behavioral outcomes was more prominent in male MCAO mice. In addition, we further identified that PARP-1 inhibitor might equivalently suppress microglial activation in males and females in vivo and in vitro. With proteomic analysis and western blotting assay, it was found that stroke-induced peroxiredoxin-1 (Prx1) expression was significantly affected by PARP-1 inhibition. Interestingly, injection of recombinant Prx1 into the ischemic core could block the anti-inflammatory effects of PARP-1 inhibitor in the experimental stroke. These findings suggest that PARP-1 inhibitor has effects on regulating microglial activation and post-stroke inflammation in males and females, and holds promise as a novel therapeutic agent for stroke with extended therapeutic time window. Efforts need to be made to delineate the actions of PARP-1 inhibition in stroke, and here we propose that Prx1 might be a critical mediator.